Rising labour costs and the future of rubber intercropping in China - Shaoze Jin; Shi Min; Jikun Huang; Hermann Waibel (International Journal of Agricultural Sustainability, 2022)
This study identifies the role of labour constraints in the use of rubber intercropping among smallholder farmers in Southwest China, drawing on a panel dataset collected from a sample of over 600 farm households in the Xishuangbanna Dai Autonomous Prefecture (XSBN). The analysis is based on two models: (i) a panel model to analyze the factors responsible for the decline in the use of rubber intercropping among smallholder farmers; (ii) an instrumental variable and endogenous switching model to assess the specific effects of off-farm labour market participation on the use of intercropping. We find a strong effect of the costs of labour on rubber intercropping. The decline in the use of intercropping has a potentially negative impact on environmental sustainability and endangers the government’s environmentally friendly rubber programme. The paper explores possibilities of how farmers can maintain intercropping under increasing labour constraints such as more engagement of elderly and female household members. This may require modifications in intercropping technologies and training. The paper recommends that the government should encourage the continuation of intercropping by a combination of well-balanced measures that include on-farm research, participatory farmer training, payment for environmental services, and effective monitoring.